The effect of training to job performance and productivity at Jabatan Kesihatan Negeri (JKN) Perak and Tenaga Nasional Berhad (TNB) Kedah / Nurul Nadiah Ahmad and Noor Zarina Abd Razak - Ahmad, Nurul Nadiah; Abd Razak, Noor Zarina (2009)
The purpose for this study are to find out the competences in Jabatan Kesihatan Negeri (JKN) Perak and Tenaga Nasional Berhad (TNB) Kedah, determine whether training is effectives to JKN Perak and TNB Kedah employees for their specific Knowledge, Skill and Abilities (KSA) and to determine the Job Performance of trainees in JKN Perak and TNB Kedah. This research uses the descriptive design. The population of workers at JKN Perak is 500 and TNB Kedah also has 500 employees. For this research, we use only 100 samples at JKN Perak and 100 at TNB Kedah. We use the 200 elements in the population at JKN Perak and TNB Kedah, and we need 50 as a sample. In this research, we use 25% from 200 samples. We distribute 60 questionnaires at JKN Perak and TNB Kedah. The feedback that we get from the respondents is 23 from JKN Perak and 27 from TNB Kedah. However, the 10 of respondents did do not return their feedback. The technique that we used to analyze data obtained from the questionnaire is Statistical Package in Social Science (SPSS) software version 13.0. The SPSS use to conduct and analyze the data after entire the questionnaire. In the data analysis, we were getting a feel for the data. We obtained the percentage (%) and frequency distribution of the nominal and interval variables of the interest.